The perspective of knowledge translation in professional master's programs in nursing (Research, Society and Development, 2021)
Objective: to know how the translation of knowledge is being used in professional master's programs in the field of Nursing. Methodology: This is a documentary study carried out from 2016 to 2019, on the websites of professional master's programs in the field of Nursing in Rio de Janeiro, guided by the following question: How do professional master's programs in the field of Nursing present in your proposal the perspective of knowledge translation? The information accessed was: focus, principles, objectives, conclusion work and product. The analysis and discussion of the data were carried out following the instructions of the method, and making a reflection in the light of the related national and international scientific literature. Results: In a global analysis of the course websites, as well as the conclusion works and products, it was noticed that there was no mention or reference of a guiding model or strategy for the translation of knowledge in professional master's programs in the field of Nursing. However, there is information in the proposals that suggest a translational perspective. Conclusion: In Brazil, knowledge translation is both a necessity and a challenge, but in order to make better use of research results, it is necessary to adapt theoretical models of knowledge translation to the Brazilian context.